The Impact of Anticipated HIV Stigma on Delays in HIV Testing Behaviors: Findings from a Community-Based Sample of Men Who Have Sex with Men and Transgender Women in New York City - Golub, Sarit A. (Mary Ann Liebert, Inc., 2013)
Treatment as prevention (TaSP) is a critical component of biomedical interventions to prevent HIV transmission. However, its success is predicated on testing and identifying undiagnosed individuals to ensure linkage and retention in HIV care. Research has examined the impact of HIV-associated stigma on HIV-positive individuals, but little work has explored how anticipated HIV stigma–the expectation of rejection or discrimination against by others in the event of seroconversion—may serve as a barrier to HIV testing behaviors. This study examined the association between anticipated stigma and HIV testing behaviors among a sample of 305 men who have sex with men (MSM) and transgender women living in New York City. Participants' mean age was 33.0; 65.5% were racial/ethnic minority; and 50.2% earned <$20,000 per year. Overall, 32% of participants had not had an HIV test in the past 6 months. Anticipated stigma was negatively associated with risk perception. In multivariate models, anticipated stigma, risk perception, and younger age were significant predictors of HIV testing behaviors. Anti-HIV stigma campaigns targeting HIV-negative individuals may have the potential to significantly impact social norms around HIV testing and other biomedical strategies, such pre-exposure prophylaxis, at a critical moment for the redefinition of HIV prevention.